COMPARISON OF PRE ORDER, IN ORDER, AND POST ORDER VISITS ON SEARCHING DATA ON BINARY TREE - Side, Syafruddin; Nur, Nikmatullah (Jurusan Matematika FST-UIN Alauddi Makassar, 2014)
Oneof interesting study of the application of graph theory is pre order, in order, and post orders. Pre order, in order, and post order are schemeo f visiting nodes in a binary tree. This study examine show the process visits of pre order, in order, post order and the comparison of pre order, in order, and post order. As well ashow the algorithms and the implementation of binary tree using pre-order, in order, and post order visit. Firstly, this study giving five trees at the same level. The five trees are visited by three visit sand then compare the results of the three visits. The results ofthe three visits are the same number of nodes visited but for the fastest order to the longest execution time is pre order visit, in order visit, and the last is post order visit. Simulation of pre order, in order, and post order visiting process in searching data on the binary tree are created in programs using Turbo Pascal 7.0.